Empowering Educators in Academic Writing: An International Community Engagement Initiative on Systematic Literature Reviews - Yulita Fairina Susanti; Cut Sjahrifa Zahirsjah; Samuel PD Anantadjaya (Journal of Sustainable Community Development (JSCD), 2026)
This study evaluates an international community development initiative titled "Literature Review Workshop," conducted through a strategic partnership between IPMI International Business School (Indonesia) and UST Angelicum College (Manila, Philippines). The initiative aimed to enhance the research competencies and pedagogical capacities of 42 educators in Manila. Operating within 21st-century educational demands, secondary and higher education teachers face the critical task of mentoring students in academic writing while advancing their own postgraduate credentials. The workshop utilized instructional scaffolding alongside hands-on digital training to instruct participants in referencing tools, synthesis matrices, and conceptual structuring via the "Funnel Approach". Evaluation indicated substantial improvements in participant competency, marked by high engagement and an immediate ability to discern research gaps. Discrepancies in baseline research knowledge were mitigated using personalized, one-on-one instructional consultations. This cross-border intervention provides a practical, scalable model for international academic institutions to drive continuous professional development (CPD) in emerging academic landscapes.